All rights reserved: Copyright protection and multinational knowledge transfers. - Ivus, Olena; Park, Walter G. (Economic Inquiry, 2022)
The copyright industry contributes to global knowledge transfers, rivaling the manufacturing industry. Creative works are media for conveying information. This paper studies the effects of copyright protection on the international licensing of US companies in the copyright‐based industries. The results show that copyrights affect technological development in creative industries as well as beyond; for example, in supporting industries that produce complementary output. The empirical analysis considers firms' selection into licensing, based on the cost of transferring creative works to host markets. The volume and likelihood of licensing rise with copyright protection when creative works are in sufficiently high demand.